Alcohol use and sociodemographic risk factors for severe intimate partner violence among women in Timor-Leste - Amin Zakaria; Yuni Asri; Heny Nurma Yunita; Vendi Eko Kurniawan; Thomas Senghore; Muhammad Solihuddin Muhtar; Christopher Blair (Faculty of Nursing Universitas Padjadjaran, 2025)
Background: Intimate partner violence (IPV) remains a significant public health concern in Timor-Leste, with sociocultural norms, economic disparities, and partner behaviors contributing to its prevalence. Understanding the associated risk factors is crucial for informing prevention strategies. Purpose: This study aimed to examine sociodemographic and behavioral factors associated with severe IPV among women in Timor-Leste Methods: A cross-sectional analysis was conducted using data from 3,694 women aged 15–49 years who participated in the 2016 Timor-Leste Demographic and Health Survey (DHS). The outcome variable was self-reported severe IPV. Independent variables included age, marital status, education, household wealth index, place of residence, geographic region, and husband/partner’s alcohol consumption. Weighted logistic regression models were used to calculate crude and adjusted odds ratios (COR, AOR) with 95% confidence intervals (CI). Results: Severe IPV was significantly associated with being aged 25–34 (AOR = 1.74; 95% CI: 1.19–2.52), being unmarried/widowed/divorced (AOR = 2.56; 95% CI: 1.33–4.92), and having a partner who consumed alcohol (AOR = 2.41; 95% CI: 1.85–3.11). Higher education and better economic status were protective against IPV. Conclusions: Alcohol consumption by partners, lower education levels, and economic disadvantage are key risk factors for severe IPV in Timor-Leste. Policies targeting alcohol reduction, women’s empowerment, and tailored regional interventions are essential to mitigate IPV and its health impacts